PERILAKU KESELAMATAN KERJA TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA KARYAWAN PT. SAR SEI. BASAU TAHUN 2018 - Linda R Sari., Renny Fitriana, (Jurnal Martenity and Neonatal, 2019)
Personal Protective Equipment (PPE) is a set of an instrument used by labor To protect all or part of his body to the predictable the potential danger in the workplace or work accident. The number of occupational accidents in Indonesia in 2011 was still highly rated from 96,400 work accidents that occurred, of which 2,144 were recorded dead and 42 others were disabled. Until September 2012 the work accident rate was in the range of 80,000 work accident cases. Based on from the data the survey scene of an accident work in PT. SAR years 2014-2016 increased. Research aims to understand the relationship between behavior occupational safety on the use of Personal Protective Equipment (PPE). Namely the levels of education, knowledge, education, attitude work , training occupational health and safety and supervision. The kind of research used is quantitative analytic observational with design research used is the cross sectional. Data analysis be done in univariat and bivariate. The result of this research is the variable who are related on the use of apd namely the levels of education (p-value= 0,030), knowledge (p-value = 0,003), attitude work (p-value= 0,000), and training occupational health and safety (p-value= 0,004). Conclusion in this research is that there a significant relation exists between behavior occupational safety on the use of apd. Suggested expain behavior occupational safety In the use of apd good and right and suggested employees in PT. SAR to always use apd in while working.